Belonging and genocide : Hitler's community, 1918-1945 - Kühne, Thomas, 1958- (Yale University Press, 2010)
No one has ever posed a satisfactory explanation for the extreme inhumanity of the Holocaust. What was going on in the heads and hearts of the millions of Germans who either participated in or condoned the murder of the Jews? In this provocative book, Thomas Kuhne offers a new answer. A genocidal society was created not only by the hatred of Jews or by coercion, Kuhne contends, but also by the love of Germans for one another, their desire for a united "people's community," the Volksgemeinschaft. During the Third Reich, Germans learned to connect with one another by becoming brother and sisters in mass crime.